Mutual transformation of the water binding state and moisture diffusion characteristics of Chinese yams during microwave freeze drying - Wang, Hui; Duan, Xu; Duan, Liuliu; Ren, Guangyue (Drying technology, 2021)
The moisture distribution changes in Chinese yam slices subjected to microwave freeze drying (MFD) were analyzed using low-field nuclear magnetic resonance (LF-NMR). During this process, the mutual transformation of the water binding state and moisture diffusion characteristics of Chinese yam were analyzed together with changes in the effective water diffusion coefficient, water content, drying rate and pore network structure. Notably, moisture migrated from a high to a low degree of freedom during the MFD process. The effective water diffusion coefficient and water migration velocity increased with increasing microwave power density, and the extent of the conversion of unbound to bound water also gradually increased. During the early stage of drying, moisture diffusion was mainly dominated by liquid phase diffusion. At later stages of drying, moisture diffusion shifted gradually from liquid phase diffusion to gas phase diffusion and was eventually dominated by the latter.